Ryzyko społeczne w procesie zmian - Rutka, Ryszard; Czerska, Małgorzata (The social risk in process of changes, 2006)
This paper focuses on rather rarely undertaken subject - social risk in a process of changes. It is divided into three chapters: presentation of essence, meaning and areas of risk in process of changes, characteristic of social aspects of this risk and methodology of its evaluation, an example of implementing methodology presented above.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 578-585